Battle for Blood: Child Custody Conflicts in Divorce – Islamic vs. Customary Law - Sarfitri, Destika Santi Putri; Damayanti, Ratih; Fidiyani, Rini; Winarsih, Winarsih; Qoiri, Mutmainah Nur; Muhsen, Jamaluddin Jamal (Universitas Negeri Semarang, 2024)
Child custody disputes following divorce often become complex legal and emotional battles, especially when religious and customary laws intersect. In many Muslim-majority societies, Islamic law (Sharia) and customary law (adat) both influence custody decisions, sometimes complementing each other but often conflicting in practice. Islamic law prioritizes the child’s welfare while emphasizing maternal custody during early childhood (hadanah) and paternal guardianship (wilayah) in later years. However, customary law, deeply rooted in local traditions, can override or modify these principles based on community norms, family ties, and social status. This study explores the legal and cultural dimensions of child custody disputes in divorce cases, analyzing the extent to which Islamic law and customary law shape judicial decisions and parental rights. While Islamic law prescribes clear guidelines, its application varies across jurisdictions, influenced by local customs and judicial interpretations. In many cases, customary norms challenge Islamic legal principles, leading to inconsistencies and gendered biases that may disadvantage mothers or overlook the best interests of the child. As globalization and legal reforms push for greater adherence to human rights and child protection standards, the tension between religious and customary laws raises critical questions about the future of custody rulings. This paper examines landmark cases, legal frameworks, and the evolving role of Islamic and customary laws in shaping custody outcomes. By comparing these perspectives, it seeks to highlight the need for harmonized legal solutions that prioritize the child’s well-being while respecting cultural and religious traditions.